Determination of trophic status and carrying capacity of floating net cages in Jatigede Reservoir - Kristina Marsela; Dadan Sumiarsa; Denny Kurniadie (Jurnal Akuakultur Indonesia, 2023)
Aquaculture activities with floating net cages are essential to increase fishery production. However, The fish cages in the Jatigede Reservoir are illegal because they are against local government regulations. However, the people affected by the dam’s construction still maintain it for economic reasons. Therefore, it is necessary to conduct research to address these problems by determining the carrying capacity of aquaculture and evaluating the trophic status of the waters. Determination of the carrying capacity of fish farming in the Jatigede Reservoir was conducted using the Beveridge method. by calculating the remaining phosphorus still available in the Jatigede Reservoir and evaluating the trophic state index based on three indicators: transparency, total phosphorus, and chlorophyll-a. The sampling was carried out by purposive sampling method. The calculation results show that the condition of the Jatigede Reservoir was eutrophic to hypertrophic with a trophic state index (TSI) value of 66-71. The results of calculating the carrying capacity of cage aquaculture using class 3 water quality standards. Indicate that Jatigede Reservoir waters can still increase fish production by 7,140.25 tons of fish/year, provided that fish replace the primary fish commodities cultivated. Keywords: aquaculture, cage aquaculture, carrying capacity, eutrophication, Jatigede Reservoir. ABSTRAK Kegiatan budidaya dengan keramba jaring apung (KJA) sangat penting untuk meningkatkan produksi perikanan. Keberadaan KJA di Waduk Jatigede merupakan kegiatan ilegal karena bertentangan dengan peraturan pemerintah setempat. Namun, masyarakat yang terkena dampak pembangunan waduk tetap mempertahankannya karena alasan ekonomi. Oleh karena itu, perlu dilakukan penelitian untuk mengatasi permasalahan tersebut dengan menentukan daya dukung perikanan budidaya dan mengevaluasi status trofik perairan. Penentuan daya dukung budidaya ikan di Waduk Jatigede dilakukan dengan menggunakan metode Beveridge dengan menghitung sisa fosfor yang masih tersedia di Waduk Jatigede dan mengevaluasi indeks status trofik berdasarkan tiga indikator yaitu transparansi, total fosfor, dan klorofil-a. Pengambilan sampel dilakukan dengan metode purposive sampling. Hasil perhitungan menunjukkan bahwa kondisi Waduk Jatigede adalah eutrofik hingga hipertrofik dengan nilai indeks kondisi trofik (TSI) 66-71. Hasil perhitungan daya dukung budidaya perikanan keramba dengan menggunakan baku mutu air kelas tiga. Perairan Waduk Jatigede masih dapat meningkatkan produksi ikan sebesar 7.140,25 ton ikan/tahun, dengan catatan ikan menggantikan komoditas ikan utama yang dibudidayakan. Kata Kunci: akuakultur, daya dukung, eutrofikasi, keramba jaring apung, Waduk Jatigede